Students' Self-Assessment of Arabic Speaking Skill - Matrokhim Matrokhim (Jurnal Internasional Pendidikan Bahasa Arab, 2021)
Abstract: This study was aimed at determining students’ self-assessment of their Arabic speaking skills. The data was gathered through distributing speaking rubric to 92 Arabic language learners. The rubric was adapted from Cherice Montgomery and was consisted of six aspects of speaking, namely pronunciation, fluency, vocabulary, content, accuracy, and comperehension and startegic competence. The data was analysed using Winstep to determine their self-assessment of speaking and how they perceive those six aspects of speaking skills. The result showed that the students identify their speaking performance as moderate level. The Wright Map revealed that content was the most difficult aspect of speaking, while pronunciation was the easiest aspect of it.